Reclaimed Water in Your Florida-Friendly Edible Landscape: EP628/ENH1364, 1/2023 - Freeman, Terra; Silvasy, Tiare; Zhuang, Yilin; Momol, Esen (EDIS, 2023)
Reclaimed water plays a significant role in water conservation, a goal of every Florida-Friendly Landscape. However, using reclaimed water on plants harvested and consumed from the home landscape must be approached with caution for vegetables, fruit trees, herbs, and other edible crops due to the risk of contamination from pathogens and salts. Before using reclaimed water in your Florida-Friendly edible garden, it is important to have a clear understanding of what it is and how it can be safely used. The target audience for this new 4-page publication of the UF/IFAS Environmental Horticulture Department is Florida residents who irrigate landscapes, including edibles, with reclaimed water. Written by Terra Freeman, Tiare Silvasy, Yilin Zhuang, and Esen Momol. https://edis.ifas.ufl.edu/ep628